Establishment of induced pluripotent stem cell line (ZZUi010-A) from an Alzheimer's disease patient carrying an APP gene mutation - Zhilei Wang; Pei Zhang; Yanlin Wang; Changhe Shi; Na Jing; Huifang Sun; Jing Yang; Yutao Liu; Xuejun Wen; Jin Zhang; Shoutao Zhang; Yuming Xu (Stem Cell Research, 2017)
Alzheimer's disease (AD) is one of the most common neurodegenerative disorders. Previous studies have identified mutations in several genes, such as amyloid precursor protein (APP), presenilin-1 (PSEN1), and presenilin-2 (PSEN2), in patients with early-onset (<65 years) familial AD. Recently, a patient with an APP gene mutation was identified; the dermal fibroblasts of the patient were obtained and a line of induced pluripotent stem cells (iPSCs) was successfully generated using the Sendai-virus (SeV) delivery system. The iPSC line will be useful for further study of the pathomechanism and drug screening for AD.